ЖАСӨСПІРІМДЕРДІҢ КҮН ТƏРТІБІ МЕН БИОЛОГИЯЛЫҚ ЫРҒАҚТЫЛЫҚТЫҢ ӨЗАРА БАЙЛАНЫСТЫЛЫҒЫН АНЫҚТАУ (Experimental biology, 2015)
The organism of children of average school age is adjusted on certain natural biological rhythms and long deviations from these rhythms generates stress, and it should affect on health of the person and its work capacity.
Keywords: organism of children; person